Controlled Synthesis of Large Single Crystals of Metal‐Organic Framework CPO‐27‐Ni Prepared by a Modulation Approach: In situ Single‐Crystal X‐ray Diffraction Studies. Issue 33 (7th May 2021) - Vornholt, Simon M.; Elliott, Caroline G.; Rice, Cameron M.; Russell, Samantha E.; Kerr, Peter J.; Rainer, Daniel N.; Mazur, Michal; Warren, Mark R.; Wheatley, Paul S.; Morris, Russell E.
Abstract: The size of single crystals of the metal‐organic framework CPO‐27‐Ni was incrementally increased through a series of modulated syntheses. A novel linker modulated synthesis using 2, 5‐dihydroxyterephthalic acid and the isomeric ligand 4, 6‐dihydroxyisophthalic acid yielded large single crystals of CPO‐27‐Ni (∼70 μm). All materials were shown to have high crystallinity and phase purity through powder X‐ray diffraction, electron microscopy methods, thermogravimetry, and compositional analysis. For the first time single‐crystal structure analyses were carried out on CPO‐27‐Ni. High BET surface areas and nitric oxide (NO) release efficiencies were recorded for all materials. Large single crystals of CPO‐27‐Ni showed a prolonged NO release and proved suitable for in situ single‐crystal diffraction experiments to follow the NO adsorption. An efficient activation protocol was developed, leading to a dehydrated structure after just 4 h, which subsequently was NO‐loaded, leading to a first NO loaded single‐crystal structural model of CPO‐27‐Ni. Abstract : A novel mixed linker modulation approach yielded large single crystals of CPO‐27‐Ni, an analogue that has not yet been able to be studied via single‐crystal X‐ray diffraction due to crystal size limitations. This study investigates the nitric oxide, an important therapeutic agent, gas loading behavior of CPO‐27‐Ni single crystals utilizing an in situ gas cell setup using synchrotron radiation.